1.90 per day: What does it say? - Sanjay G. Reddy; Rahul Lahoti (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
The World Bank's global poverty estimates suffer from deep-seated problems arising from a single source, the lack of a standard for identifying who is poor and who is not that is consistent and meaningful. The new choice of an international poverty line of 1.90 (2011 PPP) does not in any way resolve these problems. We present alternate estimates of global, regional and national poverty based on reasoning as to what the Bank's own method, consistently applied, would entail. These show an increase in the absolute number of poor since 1980 or 1990 for certain choices of poverty line. However, we recommend an approach to income poverty assessment that is altogether different, focusing directly on identifying the real requirements of human beings to attain incomedependent human capabilities.
Keywords: I32; 330; Global Poverty; International Poverty Line; World Bank; Welfare; Capability; Alternate Estimates; Purchasing Power Parity